Ecological Drivers of Habitat Use by Meso Mammals in a Miombo Ecosystem in the Issa Valley, Tanzania - D’Ammando, Giacomo; Caro, Tim; Oelze, Vicky M.; Phillips, Seth; Sime, Payton; Stewart, Fiona A.; Piel, Alexander K. (Frontiers in Ecology and Evolution, 2022)
Vast stretches of East and Southern Africa are characterised by a mosaic of deciduous woodlands and evergreen riparian forests, commonly referred to as “miombo”, hosting a high diversity of plant and animal life. However, very little is known about the small mammal communities inhabiting this heterogeneous biome. We here document the diversity and abundance of 0.5-15kg sized small mammals in a relatively undisturbed miombo mosaic in western Tanzania, using 42 camera traps deployed over a three year-period. Despite a relatively low diversity of small mammal species (n = 19), these comprised a mixture of savanna and forest species, with the latter by far the most abundant. Our results show that densely forested sites are more intensely utilized than deciduous woodlands, suggesting riparian forest within the miombo matrix might be of key importance to small mammal populations. Some species were captured significantly more often in proximity to (and sometimes feeding on) termite mounds (genus Macrotermes), as they are a crucial food resource. There was some evidence of temporal partitioning in activity patterns, suggesting hetero-specific avoidance to reduce foraging competition. We compare our findings to those of other miombo sites in south-central Africa.